AQBD ASSISTED SPECTROPHOTOMETRIC METHODS FOR THE QUANTIFICATION OF CEFIXIME TRIHYDRATE USING TWO OXIDATIVE COUPLING AGENTS: QbD assisted Spectrophotometric estimation of Cefixime trihydrate - KOKILAMBIGAI K S; LAKSHMI K S (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study focuses on developing two visible spectrophotometric methods for cefixime trihydrate (CFT) by the utilization of analytical quality by design space concept. The critical method variables were screened and optimized by factorial design. Methods: In methods A and B, CFT reacts with 3-methyl-2-benzothiazolinone hydrazone hydrochloride in an acidic medium having λmax at 630 nm and CFT reacts with 1, 10 phenanthroline (Phen) showing λmax at 510 nm, respectively. Fractional factorial design was employed for the initial screening of independent variables for both methods. The main, interaction, and quadratic effects of the most significant factors on the preferred response (absorbance) for methods A and B were studied employing central composite design (CCD) with response surface methodology. Results: The method was linear (r2=0.9983 and 0.9986 for methods A and B), accurate (mean recovery = 100.06% and 99.26% for methods A and B), precise (relative standard deviation, % relative standard deviation = 0.9214, 1.025 and 0.1919, 0.2136 for methods A and B). Conclusion: The outcome of the proposed work has evidently revealed that quality by design concept can be efficiently enforced in the optimization of spectrophotometric technique for the quantification of CFT in pharmaceutical raw materials and formulations by minimum experimental runs.